Association of Rivaroxaban vs Apixaban With Major Ischemic or Hemorrhagic Events in Patients With Atrial Fibrillation - article Editorial (Евразийский Кардиологический Журнал)
Atrial Fibrillation (AF) is associated with significant increase of stroke and other ischemic events risk. Anticoagulation to prevent ischemic strokes is a critical component of this condition management. Direct oral anticoagulants (DOACs)—with more predictable pharmacokinetics, ease of use and favorable safety and efficacy profile—are the preferred anticoagulants for patients with atrial fibrillation. This retrospective study compares major ischemic and hemorrhagic outcomes in big cohort of patients 65+ y.o. with atrial fibrillation treated with rivaroxaban or apixaban (Ray, W. A. et al., 2021).